Cutaneous Leishmaniasis: Physiopathology, Molecular Diagnostic, and Therapeutic Approaches - Abdelaali Balahbib; Asma Hmamouch; Aicha El Allam; Hikmat Douhri; Naoufal Dahaieh; Nasreddine El Omari; Jactty Chew; Long Chiau Ming; Abdelhakim Bouyahya (Progress in Microbes and Molecular Biology)
This in-depth study explores various aspects of cutaneous leishmaniasis, shedding light on the physiopathology of the infection, advances in molecular diagnostic techniques, and therapeutic approaches currently in development. Our investigation seamlessly integrates fundamental and clinical research data to provide a comprehensive perspective on this debilitating disease. Cutaneous leishmaniasis, primarily manifested through skin lesions, poses a significant diagnostic challenge. We delve into molecular diagnostic methods, especially PCR, emphasizing their crucial role in accurately detecting the infection. Simultaneously, we examine the implications of the physiopathology of cutaneous leishmaniasis, unveiling the complex mechanisms underlying this disease. In terms of treatment, we scrutinize current therapeutic approaches, highlighting limitations associated with using antimonials. Our study also explores alternative solutions, investigating the potential benefits of flavonoids and other natural compounds, thus offering innovative therapeutic perspectives. In conclusion, this research aims to enhance the understanding of cutaneous leishmaniasis from a diagnostic and therapeutic standpoint. This review is an essential resource for healthcare professionals and researchers, laying the groundwork for an integrated and holistic approach to better comprehend and treat this complex disease.